2002
DOI: 10.1017/s002202990200554x
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization, antibacterial activity and N-terminal sequencing of buffalo-milk lysozyme

Abstract: S. Lysozyme from buffalo milk was purified to homogeneity and its Nterminal amino acid sequence, biochemical properties and antibacterial spectrum were determined. The purification procedure, comprising ion-exchange chromatography using CM-cellulose and size-exclusion chromatography using Sephadex G-50, conferred 8622-fold purification and 39n3 % recovery of lysozyme. The purified enzyme migrated as a single band on sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) and native PAGE. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…However, in this study, the transmission of specific antibodies by maternal milk was not involved, since all does were seronegative for the O103 LPS. More recently, other substances present in milk have also been shown to have antimicrobial properties: defensins (19); lactoferrin (42) and its derivative, the lactoferricin (15); various enzymatic complexes like lactoperoxidase, xanthine oxidoreductase, and lysozyme (28,36,40); fucosylated oligosaccharides (10); and various fatty acids (18,27,41). It has been suggested that these components could inactivate pathogens by diverse mechanisms (growth inhibition, perturbation of adhesion) and may thereby act additively and/or synergistically (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, the transmission of specific antibodies by maternal milk was not involved, since all does were seronegative for the O103 LPS. More recently, other substances present in milk have also been shown to have antimicrobial properties: defensins (19); lactoferrin (42) and its derivative, the lactoferricin (15); various enzymatic complexes like lactoperoxidase, xanthine oxidoreductase, and lysozyme (28,36,40); fucosylated oligosaccharides (10); and various fatty acids (18,27,41). It has been suggested that these components could inactivate pathogens by diverse mechanisms (growth inhibition, perturbation of adhesion) and may thereby act additively and/or synergistically (18).…”
Section: Discussionmentioning
confidence: 99%
“…The specific activity of BM lysozyme was ten times that of CM and retained full activity after 1 min at 74°C or 30 min at 63°C (Priyadarshini and Kansal 2003). The sequence of 23 amino acid residues at the N-terminal end of buffalo lysozyme showed a 56.5% homology with CM lysozyme (Priyadarshini and Kansal 2002). Buffalo milk lysozyme inhibited four out of seven Gram-positive bacteria, but Gram-negative bacteria were resistant (Priyadarshini and Kansal 2002).…”
Section: Lysozymementioning
confidence: 97%
“…The sequence of 23 amino acid residues at the N-terminal end of buffalo lysozyme showed a 56.5% homology with CM lysozyme (Priyadarshini and Kansal 2002). Buffalo milk lysozyme inhibited four out of seven Gram-positive bacteria, but Gram-negative bacteria were resistant (Priyadarshini and Kansal 2002). Buffalo milk lysozyme was greatly influenced by the ionic strength and the concentration of metal ions in milk and in buffers (Priyadarshini and Kansal 2003).…”
Section: Lysozymementioning
confidence: 98%
“…Lysozyme has been well studied on its antibacterial activity against Gram-positive and Gram-negative bacteria, and it has been widely developed agricultural and industrial applications (During, Porsch, Mahn, Brinkmann, & Gieffers, 1999;Osman et al, 1995;Priyadarshini & Kansal, 2002). The catalytic mechanism of its bactericidal activity is hypothesized to reside in its muramidase activity, leading to degradation of the murein layer and reduction of the mechanical strength of the bacterial cell wall.…”
Section: Introductionmentioning
confidence: 99%